2010
DOI: 10.1124/jpet.110.171082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Covalent Binding ofN-Phenyl-N′-(2-chloroethyl)ureas to β-Tubulin: Importance of Glu198 in Microtubule Stability

Abstract: ureas (CEUs) are antimicrotubule agents interacting covalently with ␤-tubulin near the colchicine-binding site (C-BS). Glutamyl 198 residue in ␤-tubulin (Glu198), which is adjacent to the C-BS behind the two potent nucleophilic residues, Cys239 and Cys354, has been shown to covalently react with 1-(2-chloroethyl)-3-(4-iodophenyl)urea (ICEU). By use of mass spectrometry, we have now identified residues in ␤-tubulin that have become modified irreversibly by 1-(2-chloroethyl)-3-[3-(5-hydroxypentyl)phenyl]urea (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…It is speculated that the active site of the β-tubulin is stereo selective and the R -isomer of the branched chloroethyl group allowed a sterically favored orientation of the alkylating moiety, promoting the approach of the chlorine atom toward the sulfhydryl of Cysβ239 residue. However, subsequent work using mass spectrometry has identified that the Gluβ198, which is adjacent to the colchicine binding site behind the two potent nucleophilic residues, Cysβ239 and Cysβ354, has been shown to covalently react with CEU (129,130). None of the cysteine residues of β-tubulin was linked to the alkylating agent.…”
Section: Reported Cbsi In Preclinical Studiesmentioning
confidence: 99%
“…It is speculated that the active site of the β-tubulin is stereo selective and the R -isomer of the branched chloroethyl group allowed a sterically favored orientation of the alkylating moiety, promoting the approach of the chlorine atom toward the sulfhydryl of Cysβ239 residue. However, subsequent work using mass spectrometry has identified that the Gluβ198, which is adjacent to the colchicine binding site behind the two potent nucleophilic residues, Cysβ239 and Cysβ354, has been shown to covalently react with CEU (129,130). None of the cysteine residues of β-tubulin was linked to the alkylating agent.…”
Section: Reported Cbsi In Preclinical Studiesmentioning
confidence: 99%
“…This was also confirmed by replacing the TMP moiety of CA-4 by the CEU group resulting in molecules referred to as (Z)-1-(2-chloroethyl)-3-(4-(3-hydroxy-4-methoxystyryl)phenyl)ureas (CEU analogs to CA-4, 5d-g, Fig. 1) exhibiting antiproliferative activity (IC 50 ) at the micromolar level and that are still acylating the C-BS [14,17]. Of note, only the methoxylated phenolic moieties of CA-4 at positions 3 and 4 have been studied so far.…”
Section: Introductionmentioning
confidence: 51%
“…As mentioned earlier, CEUs such as tBCEU [24] and sBCEU [25] are acylating the glutamic acid residue in position 198 of the C-BS [13,14].…”
Section: Sceus Acylate the Glutamic Acid Residue In Position 198 Of Tmentioning
confidence: 99%
See 2 more Smart Citations